Therapies for Membranous Nephropathy: A Tale From the Old and New Millennia - Scolari, Francesco; Alberici, Federico; Mescia, Federica; Delbarba, Elisa; Trujillo, Hernando; Praga, Manuel; Ponticelli, Claudio (Frontiers in Immunology, 2022)
Primary Membranous Nephropathy (PMN) is the most frequent cause of nephrotic syndrome of the adult. If untreated, PMN may lead to end-stage renal disease; moreover, affected patients are at increased risk of complications typical of the nephrotic syndrome such as fluid overload, deep vein thrombosis and infection. The association of PMN with the HLA-DQ1 and the identification in around 70% of the cases of circulating autoantibodies mainly directed towards the phospholipase A2 receptor, supports the autoimmune nature of the disease. In patients not achieving spontaneous remission or in the ones with deteriorating kidney function and severe nephrotic syndrome, immunosuppression is required in order to increase the probability of achieving remission. Aim of this review is to discuss the evidence of the different immunosuppressive regimen employed for the management of PMN in the context of the studies published so far; the review also includes a section where the authors provide their insights on what they believe the immunosuppressive approach to the disease might be up to the evidence currently available while focusing on the still significant uncertainties.